The alchemy of food: the ritual sacrifice - Alvar Ezquerra, Jaime (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This paper is a presentation of the volume. Its aim is to explore the relationship between the food, consumers, its sacralisation and the sacrifice. Picking up some examples provided by literary sources and archaeology, the paper offers an overview throughout modern bibliography and historiographical items on sacrifice. Its central role is based in its capability to transform the common food into a divine one.
Keywords: Food; ritual banquets; sacrifice; mediations; interpretations of sacrifice